Thermal performance enhancement in evacuated tube solar collector with working fluid MWCNT/Al2O3/MgO tri-hybrid nanofluid - Sathish Thanikodi; Jayant Giri; Rathinasamy Saravanan; Shafiq Ahmad; Ahmad O. Hourani (Case Studies in Thermal Engineering)
This study is motivated-by the urgent global need to enhance the efficiency of solar thermal energy systems, particularly Evacuated Tube Solar Collector (ETSC), to meet the growing demand for renewable energy solutions in combating climate change and reducing reliance on fossil fuels. By exploring advanced tri-hybrid nanofluids, the study aims to significantly improve the thermal performance and energy capture of ETSC systems, contributing to more sustainable and efficient energy generation. ETSCs are widely used in residential, commercial, and industrial heating systems, contributing to renewable energy initiatives by reducing the dependence on conventional heating methods and lowering greenhouse gas emissions. ETSC thermal performance can be improved with nanofluid. Water/MWCNT (0.1 wt%), Water/Al2O3 (0.1 wt%), Water/MgO (0.1 wt%), and Water/50 % MWCNT, 25 % Al2O3, and 25 % MgO nanoparticle (0.1 wt%) were tested to improve ETSC thermal performance. The ETSC performance was analyzed under two different flow conditions such as 1.5L/min, and 3L/min. The result of tri-hybrid nanofluid leads to a higher thermal performance than others. Furthermore, the higher flow rate of 3L/min shows a higher thermal performance than 1.5L/min. The average enhancement achieved in terms of energy absorption rate, thermal efficiency, and exergy efficiency by tri-hybrid nanofluids were 19.1 %, 19.7 %, and 32.4 % at 3L/min respectively higher than the average of such performances at 1.5L/min flow rate. These results highlight how important it is to use nanofluids, especially Tri-hybrid nanofluids at higher flow rates, to improve the efficacy and efficiency of ETSC systems and open the door to improved energy capture and use in solar thermal applications.